Burn Care for General Surgeons and General Practitioners. - Greenhalgh, David G. (Springer International Publishing, 2016)
This textbook on burn care is focused specifically on the needs of a surgeon. It provides a "how to do" text that presents the practical strategies for initial resuscitation, skin grafting, burn-specific critical care and ultimately guide the surgeon for the best outcomes for the burn surgeon. It provides the reader with basic pathophysiology but avoids a detailed review of the molecular science of burns. Guidelines for basic care with the chapters covering the timeline used for each patient spanning from initial resuscitation (ABCs) to managing their re-socialization are provided. The text covers the key components to the initial management of the burn patient including airway, breathing and circulation. The reader is introduced to the metabolic changes of a major burn and how nutrition and pharmacologic manipulation affects these systemic effects of a burn injury. The management of burn sepsis as well as the basic concepts of wound healing of the different depths and severity of burns are covered. Another chapter covers the basic techniques of skin grafting, rehabilitation and reconstruction with a focus to optimize the cosmetic and functional outcome of the burn. Special chapters cover management of outpatient burns and pediatric injuries. Special burns - electrical, chemical, cold injuries and finally the treatment of other diseases that lead to massive skin loss are covered. Special considerations for pain, scar management, psychosocial recovery, intentional burns, burn prevention and disaster preparation complete the text. Burn Care for General Surgeons and General Practitioners provides a reference for general and plastic surgeons who are planning a career in burns. The textbook will also be a straightforward resource for the general or plastic surgeon who takes care of burns as part of their practice.